The Effect of Nanotechnology in the Formulation of Butterfly Pea Flower (Clitoria Ternatea) Extract Cream on the Antibacterial Activity of Acne-Causing Propionibacterium acnes - Chrisabela Bia; Tri Minarsih (Journal of Science and Technology Research for Pharmacy, 2025)
Acne is a chronic inflammatory skin disease caused by the bacteria Propionibacterium acnes. Common therapy using topical antibiotics can cause resistance if used long term. It is necessary to develop therapy using natural ingredients of butterfly pea flower (Clitoria ternatea) which has the potential for antibacterial activity and is made into a cream formulation with nanoparticle technology that can increase drug bioavailability. This study used an experimental method with the stages of maceration extraction of butterfly pea flowers using 96% ethanol, making nanoparticle extracts using the ionic gelation method (sodium alginate and CaCl₂), and making nanocreams using the high-energy emulsification method. The formulation formulations consisted of formula 1 extract cream, formula 2 extract nanoparticle cream, and formula 3 butterfly pea flower extract nanocream with a concentration of 5%. Particle size characterization was carried out using the Particle Size Analyzer (PSA), while the antibacterial activity test was carried out using the well diffusion method against Propionibacterium acnes bacteria. The characterization results showed that the size of the extract nanoparticles was 378 nm, the extract nanoparticle cream was 4402 nm, and the nanocream was 465 nm. Physical evaluation showed that all three formulas met good standards and were classified as O/A type creams. The nanocream formulation had the highest antibacterial activity with an average inhibition zone of 6.3 mm (moderate category), while the extract cream and extract nanoparticle cream showed lower inhibition, 4.2 mm and 1 mm respectively (weak category), so that the telang flower extract nanocream formulation was the most effective in inhibiting the growth of Propionibacterium acnes.